2011
DOI: 10.3109/02699206.2011.595527
|View full text |Cite
|
Sign up to set email alerts
|

Consonant inventories in the spontaneous speech of young children: A bootstrapping procedure

Abstract: Consonant inventories are commonly drawn to assess the phonological acquisition of toddlers. However, the spontaneous speech data that are analysed often vary substantially in size and composition. Consequently, comparisons between children and across studies are fundamentally hampered. This study aims to examine the effect of sample size on the resulting consonant inventories. A spontaneous speech corpus of 30 Dutch-speaking 2-year-olds was used. The results indicate that in order to construct and compare inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Using 60 min of speech collected monthly from 30 Dutch toddlers between the ages of 22-24 months, Van Severen et al (2012) confirmed that consonant inventory size was positively correlated with the number of words included in the sample. Their results showed that inventory size increased rapidly with sample size for small sample sizes, but reached a plateau with larger sample sizes.…”
Section: The Relationship Of Speech Sample Size To Consonant Inventormentioning
confidence: 62%
See 4 more Smart Citations
“…Using 60 min of speech collected monthly from 30 Dutch toddlers between the ages of 22-24 months, Van Severen et al (2012) confirmed that consonant inventory size was positively correlated with the number of words included in the sample. Their results showed that inventory size increased rapidly with sample size for small sample sizes, but reached a plateau with larger sample sizes.…”
Section: The Relationship Of Speech Sample Size To Consonant Inventormentioning
confidence: 62%
“…First, consonants begin to emerge in babble and speech before the age when diagnoses of ASD are stable, and studies of phonological development in infants at risk for ASD have not always examined those who receive diagnoses of ASD separately from those who do not. Second, consonant inventory size has been shown to be positively related to size of speech sample in general (Van Severen, Van Den Berg, Molemans, & Gillis, 2012), so it is unclear whether smaller consonant inventories might be an artifact of lower vocalization rate. Last, not all studies of toddlers with or at risk of ASD controlled for language level, yet (as noted above; also see Pennington & Bishop, 2009) delays in consonant production are related to delays in expressive language.…”
Section: Speech Development In Young Children With Asdmentioning
confidence: 99%
See 3 more Smart Citations